Renovating Situation Taxonomies: Exploring the Construction and Content of Fundamental Motive Situation Types. Issue 4 (15th August 2014) - Morse, Patrick J.; Neel, Rebecca; Todd, Elysia; Funder, David
Abstract The present work demonstrates a method for constructing theoretically based situational classifications and exploring their behavioral implications. Fundamental motives theory (FMT; Kenrick, Griskevicius, Neuberg, & Schaller, 2010; Kenrick, Neuberg, Griskevicius, Becker, & Schaller, 2010) proposes that humans have evolved seven specific social motives that would be differentially evoked by different situations. Experts in FMT used the Riverside Situational Q‐sort (RSQ) to describe prototypic motive‐relevant situations and the Riverside Behavioral Q‐sort (RBQ) to construct templates representing predictions of how people would behave in them. A sample of 201 undergraduate participants used the RSQ to describe situations they had experienced within the past 24 hours, and they described their behavior in each situation using the RBQ. For both the RSQ and RBQ, self‐protection and disease avoidance templates were highly similar to each other and different from mate‐seeking and affiliation templates. Participants more often reported experiencing situations similar to the mate‐seeking, affiliation, and kin care templates and less often reported experiencing situations similar to the self‐protection and disease avoidance templates. Participants' reported behavior was consistent with expectations from FMT. This study illustrates how relations between situations and behavior can be illuminated through the use of theoretically derived templates.